2.5 GHz integrated graphene RF power amplifier on SiC substrate. (January 2017) - Hanna, T.; Deltimple, N.; Khenissa, M.S.; Pallecchi, E.; Happy, H.; Frégonèse, S.
Abstract: In this work, we report the design of 2.5 GHz integrated power amplifier based on a graphene FET fabricated with thermal deposition on SiC. In this first large signal study of graphene radiofrequency power amplifiers, a power gain of 8.9 dB is achieved, the maximum reported output power and power added efficiency are 5.1 dBm and 2.2% respectively. Furthermore, graphene and Si CMOS amplifiers are compared; conclusions are drawn towards the technology enhancements to optimize the amplifiers figures of merit.